Effects of distributed pressure gradients on the pressure–strain correlations in a supersonic nozzle and diffuser. (21st February 2014) - Ghosh, Somnath; Friedrich, Rainer
Abstract Direct numerical simulation (DNS), based on high-order numerical schemes, is used to study the effects of distributed pressure gradients on the redistribution of fluctuating kinetic energy in supersonic nozzle and diffuser flow with incoming fully developed turbulent pipe flow. Axisymmetric geometries and flow parameters have been selected such that shock waves are avoided and streamline curvature remains unimportant. Although mean extra rates of strain are quite small, strong changes in Reynolds stresses and their production/redistribution mechanisms are observed, in agreement with findings of Bradshaw (J. Fluid Mech., vol. 63, 1974, pp. 449–464). The central role of pressure–strain correlations in changing the Reynolds stress anisotropy is highlighted. A Green's function-based analysis of pressure–strain correlations is presented, showing remarkable agreement with DNS data.